Evaluation of Setting Time, Compressive Strength, Microleakage and Antibacterial Properties of Nano Hydroxyapatite Incorporated GIC: An In-vitro Study - Akshada Chougaonkar; Updesh Masih; Abhilasha Manker; Neelesh Gautam; Nidhi Soni (Journal of Clinical and Diagnostic Research)
Introduction: Glass Ionomer Cement (GIC) is widely used as a restorative material, but it still exhibits some limitations that pose significant drawbacks in clinical use. The composition of Hydroxyapatite (HA) mimics the inorganic fraction of mineralised tissues such as bones and teeth. HA possesses osteoconductive and bioactive properties, making it favourable for orthopaedic and dental applications. Aim: The aim of this study was to evaluate and compare the setting time, compressive strength, microleakage and antibacterial properties of nano-HA incorporated GIC (NHa-GIC) at various concentrations with Type-II GIC. Materials and Methods: This in-vitro study was conducted in the Department of Paediatric and Preventive Dentistry at Sri Aurobindo College of Dentistry in Indore, Madhya Pradesh, India, for a duration of nine months, from May 2023 to January 2024. The study comprised five study groups as follows: Group-1-Type-II GIC (control), Group-2-NHA-GIC 4%, Group-3-NHA-GIC 8%, Group-4-NHA-GIC 10% and Group-5-NHA-GIC 15%. A total of 50 acrylic moulds containing the test material and Type-II GIC, with 10 in each group (n=10), were prepared to record the setting time, which was tested using a Gillmore needle. The compressive strength was checked using a Universal Testing Machine. Additionally, 50 primary molars were selected according to inclusion and exclusion criteria and randomly divided into five groups (n=10) to evaluate microleakage. Microleakage was assessed using the dye penetration method under a stereomicroscope. For antibacterial properties, 50 samples (n=10) were taken for each strain, i.e., Strain A: S. mutans and Strain B: L. fermentum and the disk diffusion method was employed. Thus, a total sample size of 250 was used. The preparation of GIC-NHAp was done by adding nano- HA to GIC at selected concentrations by weight/weight percentage (w/w%). The results were analysed using a one-way Analysis of Variance (ANOVA) test. Results: A statistically significant difference was observed (p<0.001) between Group-1 (GIC II) and Group-II (4% GIC-NHAp), III (8% GIC-NHAp), IV (10% GIC-NHAp) and V (15% GIC-NHAp) regarding setting time, compressive strength, microleakage and antibacterial properties. Conclusion: It can be concluded that adding NHAp crystals to GIC enhances its properties, such as compressive strength and antimicrobial efficiency, as the concentration increases. The microleakage property showed a consistent decrease with increasing concentration. However, the setting time increased with higher concentrations of NHAp in GIC.